PENGARUH FINANCIAL DISTRESS, FIRM SIZE DAN INVENTORY INTENSITY TERHADAP TAX AVOIDANCE - Nida Nurhasanah (JEKOS (Jurnal Ekonomi Dan Sosial), 2026)
This study aims to determine the effect of financial distress, firm size, and inventory intensity on tax avoidance in Food & Beverage subsector companies in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The method used in this study is quantitative. The type of data used is standard data in the form of published financial reports of Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. Samples were collected using a purposive sampling method. The number of companies used as research samples was 18 companies, with observations for 5 years from 2020–2024, resulting in a sample of 90 samples. The analysis technique in this study used panel data analysis, coefficient of determination, f-test, t-test with the help of Eviews-12 software. The results of this study indicate that financial distress, firm size, and inventory intensity have a simultaneous effect on tax avoidance. Partially, financial distress has no effect on tax avoidance. Firm size has an effect on tax avoidance and inventory intensity has no effect on tax avoidance.   Keyword: Financial distress; Firm size; Inventory intensity; Tax avoidance.